The Role of Organizational Citizenship Behavior as a Mediator on The Effect of Employee Engagement and Organizational Culture on Employee Perfomance in BPJS Ketenagakerjaan (International Journal of Scientific Research and Management (IJSRM), 2020)
The study aims to find out and analyze the relationship between employee engagement, organizational culture, organizational citizenship behavior (OCB), and employee performance. The author administered 224 participants employee engagement scale, organizational culture scale, OCB scale, and employee performance scale in BPJS Ketenagakerjaan East Java area. The data is analyzed by path analysis method in SPSS program. The result indicated that employee engagement and organizational culture affects positive significantly on OCB. Employee engagement, organizational culture and OCB also affects positive significantly on employee performance.